Exploring the awareness and interest of the younger generation in Kuala Kangsar towards Labu Sayong pottery making tradition / Nura’mirah Mat Ali and Azran Mansor - Mat Ali, Nura’mirah; Mansor, Azran (2024)
Labu Sayong is well-known for its centuries-old pottery-making tradition in Kuala Kangsar, particularly the Sayong clay pots, which symbolize local culture and craftsmanship. This vibrant tradition is still very much alive in the community. Past research emphasized the importance of preserving the traditional heritage of pottery making for future generations and the initiatives and strategies implemented to align with modernization. However, as interest in traditional crafts declines, challenges and obstacles are posed for the younger generation to carry on the tradition of pottery making. This study explores the younger generation's awareness and interest in Kuala Kangsar towards the Labu Sayong pottery-making tradition. We conducted 45 questionnaires and surveys with younger community members in Kuala Kangsar to assess their awareness, interests, and concerns towards preserving the pottery-making traditions. The findings have outlined the level of interest in pottery making among the younger generation, which also determined the current state of involvement and potential improvement opportunities and areas for improvement to foster this valuable cultural element.